COVID-19 pandemic and the situation of immigrants in enterprises - Jolanta Maj; Sabina Kubiciel-Lodzińska (Central European Economic Journal (CEEJ), 2022)
During the first (spring 2020) and second wave (autumn 2020) of the COVID-19 pandemic, Poland was among the countries with the strictest regulation, lockdown, and national quarantine. The pandemic has significantly influenced the situation of enterprises, especially for immigrants. The main aim and contribution of this paper is the analysis of the immigrant's situation during the pandemic from the perspective of companies. The research goal is the identification of strategies adopted by the firms employing immigrants, so as to providing additional help to their foreign workforce during the pandemic. For the purpose of this research, a multilevel model of the triangulation design was chosen. The qualitative research included seven in-depth-interviews with purposefully selected enterprises. The quantitative study was conducted on a sample of n=894 employers. For the purpose of the second round of research, 17 interviews with companies employing immigrants were conducted. The research showed that during the first wave of the pandemic, employers most often terminated employment with immigrants, which, however, in some cases, was the initiative of the immigrant. Some firms recognizing special needs of their foreign workforce developed strategies that manifested themselves in offering additional help to their foreign workers. The paper contributes to the literature on the situation of immigrants in terms of special treatments of immigrants as vulnerable workers and the knowledge of strategies enterprises adopted in order to help their foreign workforce during the pandemic by presenting the perspective of employers.
Keywords: J01; J15; J61; 330; COVID-19; immigration; organisational strategies; foreign workforce; labour market; diversity management